Effect of medium, pH, and inoculum size on activity of ceftizoxime and Sch-34343 against anaerobic bacteria. - Borobio, M V (1986)
The effect of two media, three pH values, and three inoculum densities on the activity of ceftizoxime and Sch-34343 against anaerobic bacteria was evaluated. The activities of both antimicrobial agents were affected by medium composition, especially against Bacteroides fragilis. Changes in pH and inoculum size affected only the activity of ceftizoxime against anaerobic bacteria.